Vascular injury in glomerulopathies: the role of the endothelium - Barbosa, Géssica Sabrine Braga; Câmara, Niels Olsen Saraiva; Ledesma, Felipe Lourenço; Duarte Neto, Amaro Nunes; Dias, Cristiane Bitencourt (Frontiers in Nephrology, 2024)
In glomerulopathies, endothelial dysfunction and the presence of histological vascular lesions such as thrombotic microangiopathy, arteriolar hyalinosis, and arteriosclerosis are related to a severe clinical course and worse renal prognosis. The endothelial cell, which naturally has anti-inflammatory and anti-thrombotic regulatory mechanisms, is particularly susceptible to damage caused by various etiologies and can become dysfunctional due to direct/indirect injury or a deficiency of protective factors. In addition, endothelial regulation and protection involve participation of the complement system, factors related to angiogenesis, the renin–angiotensin system (RAS), endothelin, the glycocalyx, the coagulation cascade, interaction between these pathways, interactions between glomerular structures (the endothelium, mesangium, podocyte, and basement membrane) and interstitial structures (tubules, arterioles and small vessels). Dysregulation of those components is also associated with the progression of renal fibrosis, since endothelial cell damage promotes endothelial-to-mesenchymal transition. Although the potential mechanisms of vascular injury have been widely described in diabetic kidney disease, hypertensive nephrosclerosis, and hemolytic uremic syndrome, they require further elucidation in other glomerulopathies. A better understanding of the pathogenesis of vascular injury in patients with glomerular diseases could contribute to the development of specific treatments for such injury.